PENINGKATAN RASA INGIN TAHU ILMU PENGETAHUAN ALAM MELALUI MODEL CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS VA SEKOLAH DASAR NEGERI KARANGROTO 02 - Bayu Purbo Asmoro; Fajar Dwi Mukti (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This study presents an increase in natural science curiosity through the CTL model in class VA students at Karangroto 02 State Elementary School. The research method used in this research is Classroom Action Research (CAR). This research is planned for two cycles, namely cycle I and cycle II, if it is not successful it will be continued in the next cycle. The CAR method used in this study is the CAR method according to Kemmis and Mc Taggart which uses a reflection spiral system consisting of several cycles. In the Kemmis and Mc Taggart methods it is explained that in one cycle or round consists of four components, namely planning, acting, observing and reflecting. Data collection techniques used are observation, interviews and documentation. The results showed that: In the first cycle, students' curiosity earned a score of 1438 with a percentage of 45%, which is a fairly good criterion. Meanwhile, in cycle II, a score of 1749 was obtained with a percentage of 87.5% which was included in the very good category. Student curiosity has increased from cycle I to cycle II.